The extensor efficiency of unicompartmental, bicompartmental and total knee arthroplasty - Garner,A; Dandridge,O; Amis,A; Cobb,J; van,Arkel R (Bone and Joint Research, 2021)
Aims: Unicompartmental (UKA) and bicompartmental (BCA) knee arthroplasty have been associated with improved functional outcomes compared to Total Knee Arthroplasty (TKA) in suitable patients, although the reason is poorly understood. The aim of this study was to measure how the different arthroplasties affect knee extensor function. Methods: Extensor function was measured for sixteen cadaveric knees and then re-tested following the different arthroplasties. Eight knees underwent medial UKA then BCA, then posterior-cruciate retaining TKA, and eight underwent the lateral equivalents then TKA. Extensorefficiency was calculated for ranges of knee flexion associated with common 46activities of daily living. Data were analyzed with repeated measures analysis of variance (=0.05). Results: Compared to native, there were no reductions in either extension moment or efficiency following UKA. Conversion to BCA resulted in a small decrease in extension moment between 70-90° flexion(p<0.05), but when examined in the context of daily activity ranges of flexion, extensor efficiency was largely unaffected. Following TKA, large decreases in extension moment were measured at low knee flexion angles(p<0.05), resulting in 12-43% reductions in extensor efficiency for the daily activity ranges. Conclusion: This cadaveric study found that TKA resulted in inferior extensor function compared to UKA and BCA. This may, in part, help explain the reported differences in 58function and satisfaction differences between partial and total knee arthroplasty.